TALABALARNING INTELLEKTUAL-KOGNITIV SALOHIYATINI RIVOJLANTIRISH DOLZARB PEDAGOGIK MUAMMO SIFATIDA - Otepbergenov, J.S. (SCIENCE and SOCIETY, 2023)
The article analyzes the issue of professional training of future teachers for these processes, emphasizing the importance of introducing digital technologies into the education system today, when raising education to a quality level is becoming one of the priority tasks of state policy. It is scientifically analyzed that it is especially important for them to be cognitive, that is, to know their field well, and to have intellectual, that is, mental potential. Moreover, the article analyzes the theory of intelligence and scientifically substantiates that increasing the intellectual and cognitive potential of students today is a scientific and pedagogical problem.